PEMBINAAN PRESTASI CLUB FUTSAL BINTANG 9 KABUPATEN GRESIK - WAHYU PRASETYO, TONY (Jurnal Kesehatan Olahraga, 2016)
ABSTRACT THE FOSTERING ACHIEVEMENT OF BINTANG 9 FUTSAL CLUB GRESIK REGENCY Name: Tony Wahyu Prasetyo SRN: 09060484056 Study Program: Bachelor Major: Education of Health and Recreation Faculy: Sport Science Institution Name: State University of Surabaya Advisor: Roy Januardi Irawan, S.Or. M.Kes Everyone needs exercise to make balance between body and suply that someone eats everyday. Besides, exercise also become people media in having recreation and entertainment which can make healty body. Exercise is not limited by people age. It means, old people and young people still need exercise in stabilizing their health. For young people, the most popular sport nowdays is futsal. Many futsal clubs reach their achievement in competition which they join. One of the futsal club is Bintang 9 Futsal Club Gresik Regency which is being the object of this research with fostering achievement as it’s focus. In this research, the researcher used descriptive qualitative method. Descriptive means giving description about the condition of something objectively. Whereas qualitative means procedure of the research which produce words both spoken and written as the result about people act that is being observed. In this research, the researcher used 2 steps in gathering the data, those were; obseration and interview. Based on the research which was done by the researcher in the fostering achievement of Bintang 9 futsal club Gresik Regency. The researcher got the data as follows: 1. The coach recruitment must has sertificate from Indonesian Football Association of Gresik. The coach must has good tallent and experience in guiding school extracuricular. Then, the team must be the winner in competition or tournamen which the school join. 2. The athletes recruitment process in Bintang 9 Futsal Club Gresik Regency is done by 2 systems. 3. The exercise and fostering achievement programs given by the coach in Bintang 9 Futsal Club Gresik Regency are chategorized as a simple practice such as: control, passing, dribble and shooting are given in more duration. 4. The falities which is belong to Bintang 9 Futsal Club Gresik Regency are nice and complete, those are: the yard which is located in Nicky Sport Center Paras Benjeng as the place of practicing. The Club also has some supporting equipment such as: 13 balls, 2 small wickets, 10 cones, and 10 pairs of vest. 5. The finance income of Bintang 9 Futsal Club Gresik Regency is from 2 sponsorship those are Sport Cellular and Sport Apotek. Each gives amount of money with nominal Rp. 2.000.000 per month. Besides, other finance is from caretaker and athletes contribution. Therefore, it can be concluded that Fostering Achievement of Bintang 9 Futsal Club Gresik Regency starts at good recruitment process, exercise and fostering achievement by qualified coaches, good finance income and sufficient facilities can improve the achievement of the club. Keywords: Fostering achievement, Bintang 9 Futsal Club Gresik Regency.